Characterization of a Multidrug-Resistant, Novel Bacteroides Genomospecies - Stephen J. Salipante; Aley Kalapila; Paul S. Pottinger; Daniel R. Hoogestraat; Lisa Cummings; Jeffrey S. Duchin; Dhruba J. Sengupta; Steven A. Pergam; Brad T. Cookson; Susan M. Butler-Wu (Emerging Infectious Diseases, 2015)
Metronidazole- and carbapenem-resistant Bacteroides fragilis are rare in the United States. We isolated a multidrug-resistant anaerobe from the bloodstream and intraabdominal abscesses of a patient who had traveled to India. Whole-genome sequencing identified the organism as a novel Bacteroides genomospecies. Physicians should be aware of the possibility for concomitant carbapenem- and metronidazole-resistant Bacteroides infections.